Simulating Stable Stochastic Systems, IV: Approximation Techniques - Crane, Michael A.; Iglehart, Donald L. (Management Science, 1975)
The previous papers in this series developed a methodology for obtaining from certain simulations confidence intervals for parameters associated with the steady-state distribution. This methodology required the simulations to contain an embedded renewal process at whose epochs the simulation started from scratch. The present paper contains four approximation techniques for obtaining confidence intervals when the simulation does not contain the required renewal process.